Are all ulvans equal? A comparative assessment of the chemical and gelling properties of ulvan from blade and filamentous Ulva. (15th July 2021) - Kidgell, Joel T.; Carnachan, Susan M.; Magnusson, Marie; Lawton, Rebecca J.; Sims, Ian M.; Hinkley, Simon F.R.; de Nys, Rocky; Glasson, Christopher R.K.
Graphical abstract: Highlights: Physicochemistry of ulvans from 4 blade and 4 filamentous species of Ulva assessed. Ulvans from filamentous species had higher molecular weights and gel strength. Ulvans from blade species had higher iduronic acid content than filamentous species. Ulva morphology drives differences in the physicochemical properties of ulvans. Abstract: Green seaweeds of the genus Ulva are rich in the bioactive sulfated polysaccharide ulvan. Herein we characterise ulvan from Ulva species collected from the Bay of Plenty, Aotearoa New Zealand. Using standardised procedures, we quantified, characterised, and compared ulvans from blade ( U. australis, U . rigida, U . sp. B, and Ulva sp.) and filamentous ( U . flexuosa, U . compressa, U . prolifera, and U . ralfsii ) Ulva species. There were distinct differences in composition and structure of ulvans between morphologies. Ulvan isolated from blade species had higher yields (14.0–19.3 %) and iduronic acid content (IdoA = 7−18 mol%), and lower molecular weight (Mw = 190−254 kDa) and storage moduli (G' = 0.1–6.6 Pa) than filamentous species (yield = 7.2–14.6 %; IdoA = 4−7 mol%; Mw = 260−406 kDa; G' = 22.7–74.2 Pa). These results highlight the variability of the physicochemical properties of ulvan from different Ulva sources, and identifies a morphology-based division within the genus Ulva .